AD, Volume 38, n° 3 & 4, 2013 - Full Issue - Journal System, (Africa Development, 2021)
Contents Claude E. Ake and the Praxis of Knowledge Production in Africa Jeremiah O. Arowosegbe ...................... 1 Militancy in the Niger Delta and the Deepening Crisis of the Oil Economy in Nigeria Chijioke Uwasomba & Victor S. Alumona ................ 21 The Potential Contribution of Love-Sex Songs to the Spread or Prevention of HIV/AIDS: The Case the Oromo of Ethiopia Workineh Kelbessa ................................... 33 Residents’ Perception of Property Rating in a Traditional African City Abel Afon .......................... 97 The Role of Trust as Informal Institution in the Informal Sector in Africa Levy Charles Odera .......................... 121